2021
DOI: 10.31234/osf.io/nrqv6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I doubt it is safe: A meta-analysis of self-reported intolerance of uncertainty and threat extinction training

Abstract: Intolerance of uncertainty (IU), the tendency to find uncertainty distressing, is an important transdiagnostic dimension in mental health disorders. Higher self-reported IU has been linked to poorer threat extinction training (i.e., the updating of threat to safe associations), a key process that is targeted in exposure-based therapies. However, it remains to be seen whether IU-related effects during threat extinction training are reliably and specifically driven by the IU construct or a particular subcomponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 55 publications
(103 reference statements)
5
27
2
Order By: Relevance
“…(4) Higher IU will be specifically associated with greater skin conductance responding and BOLD activity in the salience network (i.e. amygdala, insula, ventromedial prefrontal cortex) to learned threat vs. safe cues during uninstructed threat extinction training, similar to previous research (Morriss, Wake, et al, 2021;Morriss, Zuj, et al, 2021).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…(4) Higher IU will be specifically associated with greater skin conductance responding and BOLD activity in the salience network (i.e. amygdala, insula, ventromedial prefrontal cortex) to learned threat vs. safe cues during uninstructed threat extinction training, similar to previous research (Morriss, Wake, et al, 2021;Morriss, Zuj, et al, 2021).…”
Section: Introductionsupporting
confidence: 77%
“…Classical threat conditioning mechanisms have been typically examined to model the development and treatment of anxiety, trauma, and obsessive-compulsive disorders (Craske, Treanor, Conway, Zbozinek, & Vervliet, 2014;Jacoby & Abramowitz, 2016;McNally, 2007;Pittig, Treanor, LeBeau, & Craske, 2018). An emerging body of research has identified IU as an important modulator of classical threat conditioning mechanisms (Lonsdorf & Merz, 2017;Morriss, Wake, Elizabeth, & van Reekum, 2021;Morriss, Zuj, & Mertens, 2021). While evidence is inconclusive on the role of IU in the initial learning of threat and safety associations during acquisition training (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the lack of IU-related effect on psychophysiological measures during delayed extinction training may be due to a methodological difference. More specifically, a recent meta-analysis (Morriss, Wake, et al, 2021) highlighted that IU-related differences on skin conductance response were observed during the late part of extinction training (i.e. defined as the last 6-10 trials per CS type in studies with over 24 trials in total).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Higher IU, over STAI-T, will be specifically associated with greater skin conductance responding to learned fear vs. safe cues during delayed extinction training, like prior work of immediate extinction training (Morriss, Wake, et al, 2021;Morriss, Zuj, et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation